Evaluasi dan Perbaikan Antarmuka Pengguna pada Situs Web Arta Barber and Chill menggunakan Pendekatan Human Centered Design (HCD) - Miftahul Asyraf Nur; Ismiarta Aknuranda; Khalid Rahman (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Arta Barber and Chill has been in the barbershop world since 2010. Arta Barber and Chill provides deep shaving needs without waiting in line, but still being able to experience the quality of a premium barbershop, then equipped with health protocols that have been made through discussions with doctors to avoid the spread of the virus. In interviews with several relevant users in order to obtain information, problems were found on the Arta Barber and Chill website, such as the absence of a barber selection that matches the user's wishes and the need for a login feature so that customer data can be stored. Based on the problems found, tree testing was carried out on the initial evaluation of the website. Aspects that are measured during tree testing are success rate, directness, time spent, first click, and destination. After performing tree testing, the closed card sorting method is used in making design solutions so that the flow and navigation of the website is in accordance with user expectations, with the final result of the sitemap and in accordance with usability guidelines. The final results obtained in this study are recommendations for flow and website navigation and an increase in the value of user satisfaction. Then, the conclusions obtained from this study stated that there was a very significant increase in the value of user satisfaction.